Use of coconut fiber for particle enlargement of particulate matter in diesel exhaust - Gerente, Noel Santiago (2006)
As an alternative system to lower particulate matter in the exhaust of older diesel engine is proposed that will first seek to increase ultra-fine diesel particulate matter (DPM) in the exhaust using coconut fiber (coir) matrix and subsequently separate those agglomerates quantitatively from the exhaust. This study is focusing on the problem of agglomeration of ultrafine PM using a fiber matrix. It is intended as a feasibility study for the use of coir matrix as means to induce significant particle coagulation to sizes well above 500 mnm. This includes the design of the coconut matrix and its housing after muffler. Using a comprehensive review of aerosol dynamics, the effect of deposition and consequently agglomeration is thoroughly assessed, incorporating two models on particle deposition on fiber matrices, which not only provide theoretical support for the overall concept to agglomerate ultrafine PM, but also valuable insight for the design and layout of the fiber matrix. Two agglomerating devices were designed and fabricated with approximate filter volume of 3,000 cc and 13, 000 cc. Each device has 200 - 400 layers of coconut fiber. recorded temperature inside the device and pressure drop varies from 44 - 190˚C and 4-30 mbar, respectively, depending on the engine running time (hour), load (kW), and engine speed (RPM). A glass filter was used to capturePM 2.5 out of the exhaust using a dilution channel. PM removal at average load of 0.885 kW is 47.7% at engine speed of 900 RPM (in 0.5-hr) while 6.9% removal at actual load of 7.65 kW operating at 1100 RPM (in 2-hr). Whereas a final assessment is still to be made, an outline for subsequent work is given to provide a solution for everyday use of the agglomerating device in public transport in the Philippines.